Development of dehydrated mango-carrot leather - Bonustro, Denise Robins S.; del Rosario, Minerva Jane G. (2004)
ABSTRACT The Philippines is abounding in tropical fruits and vegetables, which however, are mostly put to waste especially during peak seasons when the supply is greater than the demand. Utilization of mango and carrot in a fruit-vegetable snack in the form of a dehydrated candy product will help minimize wastage and produce a new product for the Filipino consumers. In the study, Carabao mangoes and native carrots were processed of varying citric acid concentrations and mango:carrot ratios of 0.25, 0.30, 0.40% and 90:10, 80:20 and 70:30, respectively. These were processed using a step up process recommended by De Leon (1988) and dehydration using the Sandvik high performance dryer. The resulting samples were then subjected to sensory evaluation were rated in terms of the affective and the descriptive aspects of the samples' flavor, color, texture, aroma, consistency and overall acceptability. Results showed that the samples have no significant affective sensory differences in terms of its flavor, color and aroma but are significantly different in the texture, consistency and overall acceptability. The descriptive sensory evaluations on the other hand showed no significant differences among the samples in terms of its flavor and consistency but are significantly different in terms of color, aroma and texture. Analysis also showed that at high citric acid content, panelists preferred samples with higher carrot content while at low citric acid content, samples with high mango content were more preferred. Furthermore, the product that obtained the highest acceptability was the product having 0.45% citric acid and 80:20 mango-carrot ratio. The profile of the product consists of the following: Flavor ranges from "just right" to "sweet", color was described to be between yellow-orange to orange; the perceived aroma is distinct; the texture is not too soft but not hard; and the consistency falls between smooth to gritty. These were the attributes of the most acceptable sample.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango, Dried; Carrot, Dried; Fruit -- Preservation